Computational methods in geophysical electromagnetics - Haber, Eldad (Society for Industrial and Applied Mathematics (SIAM, 3600 Market Street, Floor 6, Philadelphia, PA 19104), 2015)
This monograph provides a framework for students and practitioners who are working on the solution of electromagnetic imaging in geophysics. Bridging the gap between theory and practical applied material (for example, inverse and forward problems), it provides a simple explanation of finite volume discretization, basic concepts in solving inverse problems through optimization, a summary of applied electromagnetics methods, and MATLAB® code for efficient computation.
Title from title screen, viewed 11/11/2014.
Keywords: Electromagnetism -- Mathematics.; Geophysics -- Mathematics.; elektronické knihy; electronic books